Determination of Canine Factor VIII-related Antigen Using Commercial Antihuman F VIII Serum - Johnstone, I B (Veterinary clinical pathology, 1980)
Factor VIII-related antigen (F VIII:AGN) in 21 canine plasma samples was assayed by immunoelectrophoresis using a rabbit anticanine F VIII serum prepared from a canine F VIII concentrate and a commercial rabbit antihuman F VIII serum. A good correlation existed (r value 0.916) between the antigen levels obtained using the two sera. In normal dogs the plasma F VIII:AGN level was 95 +/- 39% (Mean +/- SD) compared to 175 +/- 40% in dogs with severe hemophilia A and 17 +/- 15% in dogs with von Willebrand's disease. It was concluded that there was sufficient cross reactivity between canine F VIII and commercial rabbit antihuman F VIII serum to make the latter useful in the differential diagnosis of F VIII deficiencies in the dog